Bailouts in a federation: A cooperative legislature at work - Willem Sas (European Regional Science Association (ERSA), 2013)
This paper revisits the soft budget constraint problem arising in decentralised countries. Capturing the specific dynamics of political decision making in a federation, new light is shed on the incentives at work when lower-level (state) governments overborrow and are bailed out by the federal level. An intertemporal model developed by Goodspeed (2002) is supplemented by the citizen-candidate approach of Besley and Coate (1997), to further align federal decision making with reality. In our model, where a cooperative legislature of locally elected representatives decides on federal grants going to the states, voters are shown to elect candidates with a higher preference for debt accumulation than would be expected. This strategic voting behaviour not only leads to overly generous bailout policies. Also, and compared to a setting where federal decision making follows the median voter, states are proven to overborrow more inefficiently because of this federal generosity. A case can then be made for federal constituencies where politicians are elected from across the entire federation, which would neutralize these additional inefficiencies.
Keywords: 330; Fiscal decentralisation; bailouts; soft budget constraint; citizen-candidate model; cooperative legislature